Continuous and near real-time measurements of gaseous elemental mercury (GEM) from an Unmanned Aerial Vehicle: A new approach to investigate the 3D distribution of GEM in the lower atmosphere. (February 2022) - Cabassi, J.; Lazzaroni, M.; Giannini, L.; Mariottini, D.; Nisi, B.; Rappuoli, D.; Vaselli, O.
Abstract: We present the first real attempt to directly and continuously measure GEM through a Lumex RA-915 M, designed for real-time detection of mercury vapor, mounted on an UAV (Unmanned Aerial Vehicle, namely a heavy-lift octocopter), inside and outside the former Hg-mining area of Abbadia San Salvatore (Mt. Amiata, Italy), known as a GEM source. We tested the effectiveness of the UAV-Lumex combination at different heights in selected sites pertaining to both mining facilities and surrounding urban zones, shedding light on the GEM spatial distribution and concentration variability. The Lumex great sensitivity and the octocopter optimal versatility and maneuverability, both horizontally and vertically, allowed to depict the GEM distribution in the atmosphere up to 60 m above the ground. The acquisition system was further optimized by: i) synchronizing Lumex and UAV GPS data by means of a stand-alone GPS that was previously synchronized with Lumex; ii) using a vertical sampling tube (1.20 m high) connected to the Lumex inlet to overcome the rotors strong airflows and turbulence that would have affected GEM measurements; iii) supplying the octocopter with batteries for power supply to avoid the release of exhaust gases; iv) taking the advantage of the UAV ability to land in small spaces and stop at selected altitudes. The resulting dot-map graphical representations, providing a realistic 3D picture of GEM vertical profiling during the flights in near real-time, were useful to verify whether the guideline concentrations indicated by competent authorities were exceeded. The results showed that the GEM concentrations in the urban area, located a few hundred meters from the mining structures, and close to already reclaimed areas remained at relatively low values. Contrarily, GEM contents showed significant variations and the highest concentrations above the facilities containing the old furnaces, where increasing GEM concentrations were recorded at decreasing heights or downwind. Graphical abstract: Image 1 Highlights: First attempt to measure GEM in near real-time with a Lumex RA-915 M on an UAV. Test in selected sites of mining and urban zones of Abbadia San Salvatore (Italy). The method shed light on GEM spatial distribution and concentration variability. 3D dot-maps allowed to verify whether the guideline concentrations were exceeded. GEM contents achieved the highest concentrations above the old furnaces facilities.